CAPACITY AND PERFORMANCE ANALYSIS OF SUTOMO ROAD AND MERDEKA ROAD PEMATANGSIANTAR CITY - Hendra Gunawan Halawa; Wahyu Hidayat (Bulletin of Engineering Science, Technology and Industry, 2024)
Pematangsiantar City is one of the cities in North Sumatra Province that is currently developing. This city is experiencing rapid growth, so the need for efficient and reliable transportation facilities is increasing. There are two main roads in Pematangsiantar City, namely Sutomo Street and Merdeka Street, Sutomo Street and Merdeka Street are supported by trade and service activities on both sides of the road. Transportation readiness is one of the main supporters of the development of every city. Sutomo and Merdeka Street are roads located in the center of Pematangsiantar City which in terms of land function is a trade and service area. The problems on these roads are very dense and irregular economic activities, inadequate transportation and infrastructure, and the behavior of road users who park carelessly. The capacity and performance of Sutomo and Merdeka Streets, transportation activities on these roads are very hampered due to irregular parking and inadequate road capacity. The performance of Sutomo and Merdeka Streets is classified as very high so that the ability to accommodate traffic flow through both roads is low. To address these issues, it is necessary to conduct a study and build a parking building to reduce obstacles on both roads, and traffic engineering is needed so that passing vehicles do not pile up on both roads.